ADAPTASI MASYARAKAT TERDAMPAK BANJIR DI DAERAH ALIRAN SUNGAI LIMBOTO - Muh Rifaldy Happy; Ramli Utina; Marini Susanti Hamidun (JAMBURA GEO EDUCATION JOURNAL, 2022)
The purpose of this study is to analyze the adaptation of flood-affected residents in the Limboto watershed. The research method is a qualitative method that examines phenomena comprehensively with a case study approach. Interactive data analysis using three stages including; data reduction, data presentation, and conclusion drawing. The results showed that during the 2018-2022 period, there were 139 flood events in the Limboto watershed, spread over 50 sub-districts/villages in 10 sub-districts. The impacts of flooding in the Limboto watershed also vary, ranging from material, economic, health, housing losses, to the death toll. This impact has prompted changes in adaptive behavior in affected communities in the Limboto watershed, such as the creation of an early warning system, an evacuation stage, the construction of temporary embankments, new livelihoods, and providing equipment to deal with floods